Strain effect on electronic structures of graphene nanoribbons : a first-principles study - Shi, Q. W. (2011)
We report a first-principles study on the electronic structures of deformed graphene nanoribbons (GNRs). Our theoretical results show that the electronic properties of zigzag GNRs are not sensitive to uniaxial strain, while the energy gap modification of armchair GNRs (AGNRs) as a function of uniaxial strain displays a nonmonotonic relationship with a zigzag pattern. The subband spacings and spatial distributions of the AGNRs can be tuned by applying an external strain. Scanning tunneling microscopy dI/dV maps can be used to characterize the nature of the strain states, compressive or tensile, of AGNRs. In addition, we find that the nearest neighbor hopping integrals between π-orbitals of carbon atoms are responsible for energy gap modification under uniaxial strain based on our tight binding approximation simulations.